2014
DOI: 10.1111/dgd.12181
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐autonomous signal transduction in the Xenopus egg Wnt/β‐catenin pathway

Abstract: Wnt proteins are thought to bind to their receptors on the cell surfaces of neighboring cells. Wnt8 likely substitutes for the dorsal determinants in Xenopus embryos to dorsalize early embryos via the Wnt/β-catenin pathway. Here, we show that Wnt8 can dorsalize Xenopus embryos working cell autonomously. Wnt8 mRNA was injected into a cleavage-stage blastomere, and the subcellular distribution of Wnt8 protein was analyzed. Wnt8 protein was predominantly found in the endoplasmic reticulum (ER) and resided at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…We found that antisense and cis -target genes were enriched in the cell cycle, in processes including apoptosis and signaling pathways such as the TGF-beta signaling pathway and the Wnt signaling pathway. Several studies have shown that the TGF-beta signaling pathway and Wnt signaling pathway are involved in a broad spectrum of cellular functions, such as proliferation, apoptosis, differentiation, migration, and embryogenesis ( Motomura et al, 2014 ; Yu et al, 2020 ). TGF-beta signals can lead to avian ovary granulosa cell proliferation mediated by signals transduced by the cytoplasmic signal transducer Smad ( Schmierer et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that antisense and cis -target genes were enriched in the cell cycle, in processes including apoptosis and signaling pathways such as the TGF-beta signaling pathway and the Wnt signaling pathway. Several studies have shown that the TGF-beta signaling pathway and Wnt signaling pathway are involved in a broad spectrum of cellular functions, such as proliferation, apoptosis, differentiation, migration, and embryogenesis ( Motomura et al, 2014 ; Yu et al, 2020 ). TGF-beta signals can lead to avian ovary granulosa cell proliferation mediated by signals transduced by the cytoplasmic signal transducer Smad ( Schmierer et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%